Corbcula - Summary Note - Ralph Sinclair (Hello World!, 1971)
Aside from the spectacular infestations and vast benthic shell bars in streams the exotic Asian bivalve, Corbicula, has been more than a pest or a nuisance in North America. The economic losses have not been summarized but they have been severe in the field of water management.